Impact of Strategic Locations on Customer Dynamics in Business Outlets: A Case by Observation Method - Anis, Md Zohurul; Haque, A. K. M. Ahasanul; Mustaffa, Nur Fariza; Alam, Md Faisal-E (2021)
This paper investigated the impact of strategic location, a retailer's most expensive and long-term marketing mix choice, on customer dynamics. The researchers used two aspects of retail location to estimate consumer spending at a multinational café franchisee in the metropolitan area of Malaysian capital. A qualitative observation method has been applied to collect the data and analyzed it systematically. Several factors including proximity to customers, i.e. trip times, and closeness to other shops, i.e. agglomeration are measured. Both are key indicators of customer spending and, as a result, revenue for the business. Furthermore, across retail forms, location effects are diverse and frequently asymmetric. Rush hour times to a retailer's general outlet have a significantly larger effect on customer dynamics than they do on other outlets, according to the findings. Retailers are increasingly focusing on providing a better consumer experience. However, there has been a scarcity of comparable academic study on the subject. The researchers addressed particular factors in this study, emphasizing those that need further investigation.